Impact of Islamic Value as Strength of Human Resources Management Practice on the Organization Commitment; Conceptual Framework - Balla, Zienab I.; Alias, Rosima; Isa, Abdul Aziz Mat; Zaroog, Omar S.; Osman, Yousif (International Review of Management and Marketing, 2017)
The aim of this paper focuses on the implementation of Islamic human resources management (HRM) practices in organizations to boost the knowledge, performance, trust, commitment, and loyalty of employees to work smoothly with the group supervisor. In addition, these practices aid management to improve employee performance and commitment to establish a long-term association with the organization. This association greatly affects organizational outcomes for both employees and the organization to achieve their goals. Islamic HRM practices are based on Islamic principles and include various processes such as recruitment and selection, training and development, and performance appraisal. The study come out with a framework for the impact of Islamic values as strength of human resource management practice on the organization commitment. Keywords: Human Resourse, Islamic Value, Commitment JEL Classification: M10